The Idea of Designing an Amphitheater in the Besh Qardash of Bojnord (Tourist Destination and Recreational Region) with Stretch Fabric Structures - Mojgan Ghorbanzadeh (Salehan Institute of Higher Education, 2018)
One of the criteria for sustainable design is